Hemiataxia and crural hemiparesis following capsular infarct. Issue 6 (June 1983) - De Renzi, E; Nichelli, P; Crisi, G
Abstract : Two patients presenting with hemiataxia and hemiparesis on the same side are described. Both had CT scan evidence of an infarct located in the posterior limb of the contralateral internal capsule.